Transformacija organizacionno-pravovych form professional'nych klubov - Pocinkin, A. V. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The transformation of the organizational-legal forms of subjects of professional sports is an important aspect of the forming Russian model of professional sports. According to this criterion it is possible to judge those internal changes which occur in domestic professional commercial sports.